Respuesta :

Let's solve your equation step by step.

5(k - 2) - 8k= -34

Step 1: Simplify both sides of the equation.

5(k - 2) - 8k= -34

(5)(k) = (5)(-2) + - 8k= -34 (Distribute)

5k + -10 + -8k = -34

(5k + -8k) + (-10) = -34 (Combine Like Terms)

-3k + -10 = -34

-3k - 10 = -34

Step 2: Add 10 to both sides.

-3k - 10 + 10 = -34 + 10

-3k = -24

Step 3: Divide both sides by -3.

-3k\3 =-24\-3

K= 8

Answer:
K=8

Hope this helps


opening brackets
5×k -5×2- 8k=-34
multiplying
; 5k- 10 - 8k= -34
collecting like terms(6a and 7a is an example of like terms)
here the like terms are 5k and 8k because both numbers have a common variable k.
collect like terms
; 5k - 8k =-34 + 10 (be mindful of the signs, if a negative sign crosses the equality sign it becomes positive)
: -3k = -24
since we are looking on the variable k, divide both expressions by the numerical accompanying k I.e -3(note the sign)
-3k/-3=-24/-3(- cancels out - and 3 cancels out 3 in the first expression leaving k, then 3 divides 24 in the second expression giving 8)
k=8